2013
DOI: 10.1016/j.jclepro.2013.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas assessment of soybean production: implications of land use change and different cultivation systems

Abstract: Highlights:• LC GHG balance of soybean is dominated by LUC emissions.• Significant GHG variation was calculated for LUC scenarios and cultivation systems.• Tillage systems have higher GHG emissions than reduced-(no-)tillage systems.• Uncertainty in N 2 O is high and dominates cultivation GHG emissions M A N U S C R I P T A C C E P T E D AbstractThe increase in soybean production as a source of protein and oil is being stimulated by the growing demand for livestock feed, food and numerous other applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 43 publications
4
94
1
3
Order By: Relevance
“…Corn (which was assumed to constitute 70% of the feed by weight) was responsible for 41% of the impact, while soybean (20% by weight) was responsible for 12% of the impact. A lifecycle assessment of soybean production [23] found that significant greenhouse gas emissions can result from land-use change due to the expansion and cultivation of soybean. Pelletier [22] found that fishmeal production for poultry feed had a higher impact than crop production due to the fuel inputs for fishing and the energy and emissions involved in processing to obtain fishmeal and oil.…”
Section: Discussionmentioning
confidence: 99%
“…Corn (which was assumed to constitute 70% of the feed by weight) was responsible for 41% of the impact, while soybean (20% by weight) was responsible for 12% of the impact. A lifecycle assessment of soybean production [23] found that significant greenhouse gas emissions can result from land-use change due to the expansion and cultivation of soybean. Pelletier [22] found that fishmeal production for poultry feed had a higher impact than crop production due to the fuel inputs for fishing and the energy and emissions involved in processing to obtain fishmeal and oil.…”
Section: Discussionmentioning
confidence: 99%
“…The growing demand for land for biomass production results in the conversion of land to agricultural use and/or improvement of productivity on existing farmland, thus causing direct and/or indirect LUC [432]. LUC is an important driver of increased GHG emissions and may lead to altered soil organic carbon [433][434][435] and changes in a host of ecosystem services [436]. In addition, LUC is regarded as one of the major drivers of the ongoing loss of biodiversity [437].…”
Section: Sustainability Of Bioenergy Systemsmentioning
confidence: 99%
“…There are several studies that have examined how carbon footprints can be reduced from cropping systems, such as: (1) including legume crops in the farming system to reduce both N 2 O and soil carbon emissions (Paul et al, 2002;Barton et al, 2014); (2) diversification of crop rotation to reduce overall carbon footprints (Yang et al, 2014); (3) keeping crop residue and application of manure on farms to increase soil carbon levels (Peterson et al, 2013;Knudsen et al, 2014;Mukul et al, 2016); (4) application of biochar into soil to reduce nutrient leaching and N 2 O emissions (Pudasaini et al, 2012); and (4) maintaining soil moisture levels below certain percentage to reduce the amount of direct and indirect N 2 O emissions (Castanheira and Freire, 2013). However, these are outside the scope of this paper and their impacts are, therefore, not considered.…”
Section: Emissions Of N 2 O From Arable Lands Due To Crop Residuesmentioning
confidence: 99%